2015
DOI: 10.1038/laban.806
|View full text |Cite
|
Sign up to set email alerts
|

Using the facial grimace scale to evaluate rabbit wellness in post-procedural monitoring

Abstract: Rabbits are commonly used in biomedical research and might undergo potentially painful procedures during the course of a study. This column discusses the rabbit facial grimace scale as a tool for monitoring post-procedural pain and explains how it can be incorporated into a worksheet for evaluating rabbit wellness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 5 publications
0
40
0
2
Order By: Relevance
“…The face is widely used to assess emotional expression, but especially the expression of pain in individuals who cannot speak, for example some of the elderly and neonates (Rinn, 1984) and, more recently, non-human animals such as the mouse (Langford et al, 2010), rat (Sotocinal et al, 2011), horse (Dalla Costa et al, 2014), rabbit (Hampshire and Robertson 2015), and cat (Holden et al 2014). Darwin (1872) described facial expression of a wide range of emotions across species in his seminal text, "The Expression of the Emotions in Man and Animals", in which he argued that the contraction of specific muscle groups creates spontaneous facial expressions.…”
Section: Introductionmentioning
confidence: 99%
“…The face is widely used to assess emotional expression, but especially the expression of pain in individuals who cannot speak, for example some of the elderly and neonates (Rinn, 1984) and, more recently, non-human animals such as the mouse (Langford et al, 2010), rat (Sotocinal et al, 2011), horse (Dalla Costa et al, 2014), rabbit (Hampshire and Robertson 2015), and cat (Holden et al 2014). Darwin (1872) described facial expression of a wide range of emotions across species in his seminal text, "The Expression of the Emotions in Man and Animals", in which he argued that the contraction of specific muscle groups creates spontaneous facial expressions.…”
Section: Introductionmentioning
confidence: 99%
“…Since we can measure its severity from a patients’ subjective report, it is also considered that the accurate evaluation of pain in animals remains impossible. Previous reports demonstrated that spontaneous pain in animals such as rats, mice, horses, and rabbits could be evaluated using the changes of facial expressions, and that patients with severe nausea change their facial expression to signify distress (Langford et al, 2010; Sotocinal et al, 2011; Hampshire and Robertson, 2015; Dalla Costa et al, 2016). We observed that rats made grimaces after the administration of cisplatin; therefore, we hypothesized that changes in facial expression can be used as a method to evaluate the nausea-like response in rats.…”
Section: Discussionmentioning
confidence: 99%
“…It would be preferable to use a more realistic distress metric. While different methods for quantifying pain and distress in laboratory animals are being developed, the relationships between distress and change in effects such as changes in relative liver weight are unknown. In order to evaluate strategies for experimental design involving research animals there is a need of new tools and concepts to investigate if it is more ethically and scientifically efficient to use many animals at lower doses with subtle effects or few animals at higher doses with clear effects.…”
Section: Discussionmentioning
confidence: 99%